IMPACT OF RED CELL AND PLATELET DISTRIBUTION WIDTH IN PATIENTS OF MEDICAL INTENSIVE CARE UNIT - Dubey, Ayush; Kumar , Sunil; Lahole, Swapnil; Chaturvedi, Saurav (International Journal of Psychosocial Rehabilitation, 2020)
The study is being conducted to observe the impact of both RDW and PDW combined and to evaluate its prognostic importance with death in critically ill patients admitted in intensive care unit.To predict outcome in patients admitted in medical intensive care units in terms of length of ICU stay, need for ventilator and mortality.To compare Red cell distribuition width and Platlet distribuition width with APACHE 4 scoreIn this cross sectional study, in all enrolled 100 patients admitted in medical intensive care unit. RDW and PDW were measured and compared with APACHE IV score. Data collection was done on demography, ICU stay, days on mechanical ventilation and mortality. The collected data was analyzed and continuous variables were expressed as mean ± standard deviation.As RDW and PDW increases, mortality, use of mechanical ventilator and length of ICU stay Increases RDW and PDW monitoring may predict outcome in MICU patients.